The Importance of Building Networks and Collaboration Between Entrepreneurs for Business Growth - Mattayang, Amin Nurfitra; Umrawati, Sitti; Kamaruddin, Syamsu A. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Network building and collaboration between entrepreneurs is one of the main factors that plays an important role in supporting business growth. A strong network can open wider market opportunities, introduce access to important resources, and speed up the innovation process. Meanwhile, collaboration between entrepreneurs provides space to share experiences, reduce operational costs, and create more effective business solutions. This article explores how entrepreneurs can leverage networking and collaboration to accelerate business growth and provides real-world examples of best practices. This research also discusses the challenges faced in building networks and collaboration and how to overcome them.